Palaeozoic tectonic evolution and magmatism in the Kalatag area, East Tianshan, NW China: Evidence from the geochronology and geochemistry of intrusive rocks. Issue 7 (22nd March 2022) - Zhang, Zhenlong; Yang, Fuquan; Zhou, Taofa; Geng, Xinxia; Zhang, Zhixin; Yang, Chengdong
Abstract : The Kalatag area contains many intrusive rocks of Late Ordovician to Permian age and hosts polymetallic deposits that are associated with magmatism. It is a key area for revealing the nature and genesis of the Palaeozoic rocks in East Tianshan. The intrusive rocks of different periods preserve useful information regarding the tectonomagmatic history of the Kalatag area. Zircon U–Pb geochronological, Hf isotopic, Sr–Nd isotopic, and whole‐rock geochemical analyses are reported for the intrusions from the Meiling ore district, Yudai ore district, and Kalatag pluton to reveal their petrogenesis and geodynamic setting. The LA–ICP–MS zircon U–Pb analyses suggest that the quartz diorite from the Kalatag pluton formed at 420–432 Ma, and the quartz diorite porphyry from the Yudai ore district formed at 436–439 Ma. The zircons from the quartz diorite and quartz diorite porphyry mainly yield high εHf (t) values (12.2–16.2) and very young Hf model ages (TDM  = 0.41–0.56 Ga; TDM C  = 0.49–0.56 Ga), which are consistent with a depleted mantle origin. The geochemical characteristics of the granites and quartz diorites from the Kalatag pluton and diorite porphyry from the Meiling ore district exhibit typical subduction‐related features such as enrichment in LILEs and LREEs and depletion in HFSEs. These diorites have moderate Mg # (30–47), positive εNd (t) values (4.2–5.6), and young Nd model ages (0.62–0.83 Ga), which are consistent with a depleted mantle origin that is accompanied by limited crustal assimilation. Based on the regional geology and geochemical evidence and previous studies, the Ordovician–Carboniferous rocks from the Kalatag area are considered to have formed in an island‐arc setting and were probably formed by a subduction event. Abstract : Petrochemical classification diagrams and histogram of age for intrusive rock from the Kalatag area. Schematic diagram showing a subduction of Oceanic plate during Late Ordovician‐Silurian and Carboniferous for the East Tianshan.